Opportunities for play in paediatric healthcare environments: a scoping review - Yu, Clarissa; Weaver, Sophie; Walker, Meaghan; Hess, Julia; Mac, Amanda; Ross, Timothy (Frontiers in Rehabilitation Sciences, 2024)
Play spaces are important components of paediatric healthcare environments. They provide children with critical opportunities to experience the social, emotional, and developmental benefits of play while in healthcare settings for appointments or hospitalizations. These spaces can help to mitigate stress, provide a sense of normalcy in unfamiliar environments, and facilitate social engagement for children and their families. Given the benefits of play spaces in paediatric healthcare settings, it is important to understand how these spaces can be designed to enhance children’s inclusion and quality of care. The aim of this scoping review was to explore the current understanding of paediatric play space design. Using search terms related to children, health care, and play space, six interdisciplinary databases were searched over a 30-year period. The search found 2,533 records from which eighteen were included for review. Findings suggest that although it is well-documented that play spaces offer valuable social and emotional benefits, little is known about the specific design features that can and should be incorporated to enhance play opportunities and ensure that they benefit all children and families. Further, the literature mostly considers play spaces in the context of designated play or recreational rooms. Scholars are encouraged to consider how play opportunities can be incorporated into the designs of paediatric healthcare environments beyond the boundaries of these rooms. Future studies should also consider the diversity of play space users, including children of varying ages and abilities, to create more accessible and inclusive paediatric play spaces for children and their families. Advancing knowledge on play space design can help to optimize the quality of these important spaces and to ensure their designs meaningfully enhance children’s play experiences and quality of care.